Consumers' differential perception towards financial products: The key-driver of purchase decision by social media - Behera, Y.D.P., Sahoo, S.K. and Sahoo, T.R. (Abhigyan)
The evolution of social media has not only brought the socialisation into next higher level, but also justified to be a better marketing channel for the financial product. In this context, the research problem of this study can be defined as (3z(Bcan the purchase decision-making of any particular financial product be driven by social media that form differential perception along the moderation effect of past experience?(3y (BThe current study is following descriptive research design, where relevant literature relating to social media, differential perception, the role of past experience, and decision making of financial products' customers enabled the authors to propose a model. Other major results of this study refer that four major dimensions of social media are driving the 'differential perception'. The level at which differential perception will be accelerated or decelerated, at that level purchase decision can be changed with the moderation effect of customers' past experience with financial products. - Reproduced s
Keywords: Social media, Financial product consumers, Purchase decision, Key driver, Differential perception, Past experience